Factors predicting the active treatment of renal angiomyolipoma: 30 years of experience in two tertiary referral centers - Daché, Arnaud; Fatica, Richard; Herts, Brian R.; McLennan, Gordon; Remer, Erick M.; Haber, Georges-Pascal; Ouzaid, Idir (Frontiers in Surgery, 2023)
Introduction and Objective: The aim of this study was to identify clinical features representing predictive factors of active treatment (AT) as compared to active surveillance (AS) for renal angiomyolipoma (AML). Patients and methods: From 1990 to 2020, patients referred to 2 institutions for a renal mass, and diagnosed with an AML based on typical features on CT were included in the analysis. The study population was divided into two groups based on the treatment received: active surveillance (AS) or active treatment (AT). Age, gender, tuberous sclerosis syndrome, tumor size, contralateral kidney disease, renal function, year of diagnosis, and symptoms at presentation were assessed as potential predictive factors of active treatment using a logistic regression model in univariate and multivariate analysis. Results: Overall, 253 patients (mean age 52.3 ± 15.7 years; 70% female; 70.9 % incidentally diagnosed) were included in the analysis. One hundred and nine (43%) received AS, whereas 144 (57%) were actively treated. On univariate analysis, age, tuberous sclerosis complex syndrome, tumor size, symptoms at presentation, and contralateral kidney disease were predictors of AT. Only tumor size (p<0.001) and the year of diagnosis (p<0.001) remained significant on multivariable analyses. The likelihood of being managed with AS evolved over the study period and was 50% and 75% when diagnosed before and after 2010 respectively. With respect to size, 4 and 6 cm tumors had a probability of being treated with AS of 50% and 25% respectively. Conclusion: The present analysis from a high volume institutions provides evidence that the management of renal masses with typical radiological features of AML have markedly changed over the last three decades with a trend towards AS over AT. Tumor size and the year of diagnosis were significant factors for the treatment strategies.